Age- and cognitive load–related variability and entropy of gait: integrating coefficient of variation, median absolute deviation, and permutation entropy of spatiotemporal parameters into the Semmelweis Study gait assessment framework - Peter Mukli; Mihaly Muranyi; Ágnes Lipecz; Zsofia Szarvas; Tamás Csípő; Mónika Fekete; Vince Fazekas-Pongor; Anna Peterfi; Ágnes Fehér; Norbert Dosa; Csilla Kaposvári; Anna Aliquander; et al. (GeroScience, 2026)
Aging profoundly alters the neuromotor and cognitive systems that support gait control, leading to increased variability and instability that predict functional decline and dementia risk. In this pilot study, conducted to inform the design of the Semmelweis Study gait assessment pipeline, we examined how aging and cognitive load influence the magnitude and temporal organization of gait fluctuations. The Semmelweis Study is a large, prospective workplace cohort at Semmelweis University designed to identify the determinants of unhealthy aging and the mechanisms that preserve functional resilience across the life course. One hundred three adults aged 23–87 years completed single- and dual-task walking trials on a 20-foot pressure-sensitive walkway. Gait variability was quantified using the median absolute deviation (MAD) and coefficient of variation (CoV) of key spatiotemporal parameters, while permutation entropy (PE) captured the complexity of stride-to-stride dynamics. Aging was associated with progressive increases in both the variability (MAD, CoV) and changes in orderliness (PE) of gait fluctuations, particularly under dual-task conditions, suggesting a dual contribution of neuromotor degradation and compensatory recruitment of higher-order control processes. The amplification of these effects during cognitive load highlights the vulnerability of cognitive–motor integration with advancing age. By integrating robust, relative, and nonlinear variability metrics within a unified analytical framework, this study provides a multidimensional characterization of gait control and establishes sensitive indicators for detecting early functional decline. Within the translational framework of the Semmelweis Study, these quantitative gait measures—together with vascular, metabolic, and cognitive assessments—are expected to serve as informative components of a comprehensive biomarker system aimed at identifying early determinants of unhealthy brain aging and guiding preventive strategies to promote healthy longevity.

Age-related and dual task-induced gait alterations and asymmetry: optimizing the Semmelweis Study gait assessment protocol - Peter Mukli; Mihaly Muranyi; Ágnes Lipecz; Zsofia Szarvas; Tamás Csípő; Anna Ungvari; Mónika Fekete; Vince Fazekas-Pongor; Anna Peterfi; Ágnes Fehér; Norbert Dosa; Noémi Mózes; et al. (GeroScience, 2025)
Gait alterations are recognized as early markers of age-related decline and cognitive impairment. Dual-task assessments, which impose cognitive load while walking, provide valuable insights into gait control limitations and cognitive-motor interactions in aging populations. This study evaluates age-related and cognitive load-induced changes in gait parameters, with a particular focus on asymmetry, and aims to optimize the gait assessment protocol for the Semmelweis Study framework. The Semmelweis Study is a large-scale workplace cohort investigating the determinants of unhealthy aging and promoting healthy brain aging by identifying risk factors and protective mechanisms influencing vascular, metabolic, and neurocognitive decline. As part of this initiative, gait analysis is emerging as a critical tool for assessing functional aging, detecting early signs of mobility and cognitive impairment, and contributing to biological age assessment. A cross-sectional analysis was conducted on adults aged 23 to 87 years using a pressure-sensitive walkway system. Participants were evaluated under single-task conditions (normal walking) and dual-task conditions (walking while performing a concurrent cognitive task). Spatiotemporal gait parameters, asymmetry indices, and dual-task costs were analyzed to assess age-related changes in gait performance and cognitive-motor interactions. Aging was associated with significant reductions in gait speed, step length, and stride length, along with a corresponding increase in gait asymmetry. Dual-task conditions exacerbated these alterations, indicating age-related impairments in cognitive-motor integration. Asymmetry indices were sensitive to aging effects, suggesting their potential as biomarkers for functional decline. The dual-task cost on gait was significantly greater in older adults, reinforcing the interplay between cognitive and motor systems in aging. Age-related gait alterations, particularly under cognitive load, underscore the importance of comprehensive gait assessments in aging research. Our findings contribute to the optimization of the Semmelweis Study gait assessment protocol by identifying key gait parameters that capture functional decline and biological aging. Integrating dual-task gait analysis into large-scale epidemiological studies has the potential to enhance early detection of brain health decline, refine biological age estimation, and guide targeted interventions to support healthy aging and neuromotor resilience.

Advancing prediction of age-related vascular cognitive impairment based on peripheral and retinal vascular health in a pilot study: a novel comprehensive assessment developed for a prospective workplace-based cohort (The Semmelweis Study) - Tamas Csipo; Agnes Lipecz; Peter Mukli; Anna Péterfi; Zsofia Szarvas; Anna Ungvari; Lamyae El Alaoui; Márton Sándor; Attila Kállai; Mónika Fekete; Gábor Á. Fülöp; Stefano Tarantini; et al. (GeroScience, 2024)
With a growing elderly population in the European Union, age-related diseases associated with unhealthy aging pose increasing public health challenges, including a loss of independence and heightened societal burdens. The Semmelweis Study, a prospective occupational cohort study in Hungary, seeks to identify determinants of unhealthy aging, focusing on the complex relationship between lifestyle, environmental, occupational factors, and the development of chronic age-associated diseases, including age-related vascular cognitive impairment (VCI). The primary objective of this pilot study was to establish a robust, high-throughput assessment methodology to comprehensively evaluate both peripheral and cerebrovascular health to provide a solid foundation for the forthcoming Semmelweis Study framework. The study involved 49 participants aged 23 to 87 years, and it assessed multi-domain cognitive performance through an automated battery of tests (CANTAB). Vascular health was comprehensively evaluated using laser speckle contrast imaging (LSCI), flow-mediated dilation (FMD), static and dynamic retinal vessel analysis (SVA, DVA), and measurements of vascular stiffness. The retinal microvasculature, which closely mirrors the cerebral circulation in anatomy, physiology, and pathophysiology, provided a unique window for examination. Optical imaging through SVA and DVA enables the identification of structural and functional changes in the central nervous system’s microcirculation, which are highly relevant to the pathogenesis of VCI. Subsequently, the collected measures were integrated into vascular health indices using principal component analysis (PCA) and the relationship to the age and cognitive status of study participants was explored. These comprehensive vascular health indices demonstrated a correlation not only with age but also with cognitive performance. This methodology holds promise for providing novel insights into the intricate interplay between vascular and cognitive health within the context of the Semmelweis Study.

Optimizing cardiopulmonary rehabilitation duration for long COVID patients: an exercise physiology monitoring approach - Zsofia Szarvas; Monika Fekete; Gergo Jozsef Szollosi; Katica Kup; Rita Horvath; Maya Shimizu; Fuko Tsuhiya; Ha Eun Choi; Huang-Tzu Wu; Vince Fazekas-Pongor; Kinga Nedda Pete; Renata Cserjesi; et al. (GeroScience, 2024)
The presence of prolonged symptoms after COVID infection worsens the workability and quality of life. 200 adults with long COVID syndrome were enrolled after medical, physical, and mental screening, and were divided into two groups based on their performance. The intervention group ( n = 100) received supervised rehabilitation at Department of Pulmonology, Semmelweis University with the registration number 160/2021 between 01/APR/2021–31/DEC/2022, while an age-matched control group ( n = 100) received a single check-up. To evaluate the long-term effects of the rehabilitation, the intervention group was involved in a 2- and 3-month follow-up, carrying out cardiopulmonary exercise test. Our study contributes understanding long COVID rehabilitation, emphasizing the potential benefits of structured cardiopulmonary rehabilitation in enhancing patient outcomes and well-being. Significant difference was found between intervention group and control group at baseline visit in pulmonary parameters, as forced vital capacity, forced expiratory volume, forced expiratory volume, transfer factor for carbon monoxide, transfer coefficient for carbon monoxide, and oxygen saturation (all p < 0.05). Our follow-up study proved that a 2-week long, patient-centered pulmonary rehabilitation program has a positive long-term effect on people with symptomatic long COVID syndrome. Our data showed significant improvement between two and three months in maximal oxygen consumption ( p < 0.05). Multidisciplinary, individualized approach may be a key element of a successful cardiopulmonary rehabilitation in long COVID conditions, which improves workload, quality of life, respiratory function, and status of patients with long COVID syndrome.

Exposome and unhealthy aging: environmental drivers from air pollution to occupational exposures - Tamas Pandics; David Major; Vince Fazekas-Pongor; Zsofia Szarvas; Anna Peterfi; Peter Mukli; Rafal Gulej; Anna Ungvari; Monika Fekete; Anna Tompa; Stefano Tarantini; Andriy Yabluchanskiy; et al. (GeroScience, 2023)
The aging population worldwide is facing a significant increase in age-related non-communicable diseases, including cardiovascular and brain pathologies. This comprehensive review paper delves into the impact of the exposome, which encompasses the totality of environmental exposures, on unhealthy aging. It explores how environmental factors contribute to the acceleration of aging processes, increase biological age, and facilitate the development and progression of a wide range of age-associated diseases. The impact of environmental factors on cognitive health and the development of chronic age-related diseases affecting the cardiovascular system and central nervous system is discussed, with a specific focus on Alzheimer’s disease, Parkinson’s disease, stroke, small vessel disease, and vascular cognitive impairment (VCI). Aging is a major risk factor for these diseases. Their pathogenesis involves cellular and molecular mechanisms of aging such as increased oxidative stress, impaired mitochondrial function, DNA damage, and inflammation and is influenced by environmental factors. Environmental toxicants, including ambient particulate matter, pesticides, heavy metals, and organic solvents, have been identified as significant contributors to cardiovascular and brain aging disorders. These toxicants can inflict both macro- and microvascular damage and many of them can also cross the blood–brain barrier, inducing neurotoxic effects, neuroinflammation, and neuronal dysfunction. In conclusion, environmental factors play a critical role in modulating cardiovascular and brain aging. A deeper understanding of how environmental toxicants exacerbate aging processes and contribute to the pathogenesis of neurodegenerative diseases, VCI, and dementia is crucial for the development of preventive strategies and interventions to promote cardiovascular, cerebrovascular, and brain health. By mitigating exposure to harmful environmental factors and promoting healthy aging, we can strive to reduce the burden of age-related cardiovascular and brain pathologies in the aging population.